Improvements of 210Po determination method in thermal water samples - Van Hao , Duong; Nguyen Dinh, Chau; Phan Trong, Trinh; Chu Tien, Trung (Vietnam Journal of Earth Sciences, 2021)
Determination of naturally radionuclides have been known well as an important topic in environmental study in recently. One of the most toxic radioisotope in nature, a daughter product of 238U decay chain is 210Po (polonium). The improvement and optimizations methods for determination of this attractive isotope are still presenting so far. In this paper, a new improved method was elaborated for 210Po determination in thermal water sample. In the proposed method, analytical optimization of spontaneous/auto deposition does not use Teflon cup, magnetic stirring or any preparing equipment/item only normal glass and a side of square silver. In addition, the optimization was neglected with absent of purification of polonium (Liquid-liquid extraction methods/Ion exchange chromatography/Extraction chromatographic separations). The outcome of optimal procedure were simplify, less time consuming, great reduction of costs with chemical recovery >80% and could apply for any liquid environmental samples.